Brazilian red pepper fruit essential oil (Schinus terebinthifolius) may replace monensin in high concentrate diets for feedlot lambs - Bertoloni, Analisa Vasques; Polizel, Daniel Montanher; Ferraz Junior, Marcos Vinícius de Castro; Miszura, Alexandre Arantes; Barroso, José Paulo Roman; Martins, André Storti; Sardinha, Lairana Aline; Limede, Arnaldo Cintra; Oliveira, Gabriela Bagio; Ferreira, Evandro Maia; Pires, Alexandre Vaz (Brazilian Journal of Veterinary Research and Animal Science, 2019)
Essential oil (EO) from Brazilian red pepper fruit contains compounds with antimicrobial activity, and could be possible substitutes for the antibiotics commonly used in ruminant nutrition. Te objectives of the present study were to evaluate the efects of the Brazilian red pepper fruit EO (Schinus terebinthifolius) as a substitute for monensin on performance, carcass characteristics and meat of lambs fed high concentrate diets. Forty-eight lambs were used, 24 males (20 ½ Dorper × ½ Santa Inês and 4 Santa Inês) and 24 females (24 ½ Dorper × ½ Santa Inês), with 21.54 ± 0.88 kg of initial body weight (BW) and 78 ± 2.4 days of age, in a randomized complete block design. Te experiment lasted 56 days, divided into 2 periods of 28 days each. Te treatments were defned by the inclusion in diets of 8 ppm of monensin (MON), and the doses 0.14% (14EO), 0.28% (28EO) and 0.42% (42EO) of red pepper fruit EO. Te additives were included in a base diet with a 10:90 of forage to concentrate ratio. At the end of 56 days, 32 animals were slaughtered for the measurement of carcass parameters and meat composition. Tere was no interaction among treatments and periods for average daily gain (P = 0.08), DM intake (P = 0.36), feed efciency (P = 0.24) and oocyst of Eimeria ssp. in feces (P = 0.46). Te treatments did not afect (P > 0.05) the average daily gain (ADG), dry matter intake (DMI) and feed efciency. Lambs fed diets containing monensin had less (P < 0.01) oocyst/g compared with the diet 14EO. Tere was no efect of diets on carcass characteristics. Te treatments with higher doses of the Brazilian red pepper fruit EO had reduced mineral content of meat compared to monensin. Te red pepper fruit EO demonstrated the potential to replace monensin in feedlot lambs fed high concentrate diets, maintaining performance and carcass characteristics. However, the monensin has greater capacity to control coccidiosis in feedlot lambs.